Treatise on divine unity according to the doctrine of the Christians - Yaḥyā Ibn-ʿAdī 893-974 (Eastern Christian texts, 2024)
"How do intellectual traditions interact? This is the fundamental question driving this book, which explores a case study set in the early Islamicate world: the Treatise on Divine Unity According to the Doctrine of the Christians by the Christian-Arabic theologian and philosopher Yahya ibn 'Adi (d. 974). The book attempts to contextualise the treatise and its intellectual environment by exploring the interplay between philosophy, Christian theology and Islam. This volume includes a revised Arabic text of Samir's 2015 edition, collated with the manuscript Tehran, Madrasa-yi Marwi 19, recently discovered by prof. Robert Wisnovsky"--